2001
DOI: 10.1128/aem.67.5.2319-2325.2001
|View full text |Cite
|
Sign up to set email alerts
|

Shewanella putrefaciens Adhesion and Biofilm Formation on Food Processing Surfaces

Abstract: Laboratory model systems were developed for studying Shewanella putrefaciens adhesion and biofilm formation under batch and flow conditions. S. putrefaciens plays a major role in food spoilage and may cause microbially induced corrosion on steel surfaces. S. putrefaciens bacteria suspended in buffer adhered readily to stainless steel surfaces. Maximum numbers of adherent bacteria per square centimeter were reached in 8 h at 25°C and reflected the cell density in suspension. Numbers of adhering bacteria from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(81 citation statements)
references
References 43 publications
1
78
0
2
Order By: Relevance
“…Shewanella oneidensis has two type IV pilin gene clusters (MSHA and tapABCD) that may be important as host colonization factors, phage receptors, and mediators of DNA transfer. Additionally, S. oneidensis is known to attach to solid surfaces (i.e., iron and manganese oxides) and form biofilms 13,27,28 , and MSHA plays a role in biofilm formation in V. cholerae 29,30 .…”
Section: Online)mentioning
confidence: 99%
“…Shewanella oneidensis has two type IV pilin gene clusters (MSHA and tapABCD) that may be important as host colonization factors, phage receptors, and mediators of DNA transfer. Additionally, S. oneidensis is known to attach to solid surfaces (i.e., iron and manganese oxides) and form biofilms 13,27,28 , and MSHA plays a role in biofilm formation in V. cholerae 29,30 .…”
Section: Online)mentioning
confidence: 99%
“…It has been hypothesized that direct interaction of Shewanella cells with, or close proximity to, an appropriate surface facilitates the deposition of electrons (Das and Caccavo, 2000;Gorby et al, 2006;McLean et al, 2010). In fact, Shewanella species have been demonstrated to adhere to various surfaces and form biofilms (Bagge et al, 2001;Thormann et al, 2004Thormann et al, , 2005Thormann et al, , 2006Teal et al, 2006;McLean et al, 2008a;Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Since S. oneidensis and related Shewanella species have been isolated from corroding steel pipelines (Semple & Westlake, 1987;Dubiel et al, 2002), a mechanistic understanding of the role of Shewanella biofilm formation and metabolic activity may help to facilitate corrosion control (Lee & Newman, 2003). The capacity of S. oneidensis to attach to and detach from solid surfaces and to form biofilms has already been described in a number of applications and studies (Bagge et al, 2001;Little et al, 1998;Thormann et al, 2004Thormann et al, , 2005. It has recently been suggested that two type IV pilin gene clusters, MSHA (mannosesensitive haemagglutinin) and tapABCD, could be involved in this process (Heidelberg et al, 2002), in the same way that MSHA plays a role in biofilm formation by Vibrio cholerae (Chiavelli et al, 2001).…”
Section: Introductionmentioning
confidence: 99%